Effectiveness of Flash Card Media To Improve Early Childhood Hijaiyah Letter Recognition - Nur Aisyah; Ridwan Ridwan; Huda Huda; Wiwin Faisol; Hasanah Muawanah (LPPM Universitas Pahlawan Tuanku Tambusai, 2022)
This study aims to analyze the effectiveness of Flash Card media to improve early childhood hijaiyah letter recognition conducted at Raudlatul Athfal Al Hanafiah Kotaanyar Probolinggo using qualitative methods of case study types. Participants in this study as many as three people, namely the principal, class A teacher, and class B, were taken with a purposive sampling approach. The results of research on the effectiveness of Flash Card media to improve the introduction of early childhood hijaiyah letters show that the analysis of the needs of flashcard media is the first step in researching the application of Flash Card media. Second, create a learning design by RPPH guidelines by applying flash card media. Third, the implementation of flashcard media consisting of 29 hijaiyah letter flashcards, which then early childhood takes cards one by one